Communication yearbook 8 - Bostrom, Robert N.; Westley, Bruce H. (Sage Publications, 1984)
The Communication Yearbook annuals publish diverse, state-of-the-discipline literature reviews that advance knowledge and understanding of communication systems, processes, and impacts across the discipline. Sponsored by the International Communication Association, each volume provides a forum for the exchange of interdisciplinary and internationally diverse scholarship relating to communication in its many forms. This volume re-issues the yearbook from 1984.